Pengaruh Gaya Kepemimpinan, Budaya Organisasi, dan Motivasi Terhadap Kepuasan Kerja Bendahara Pengeluaran Pembantu Di Universitas Ptnbh - Ulum, Nafi' Fahrur; Nuswantara, Dian Anita; Pujiono, Pujiono (Riviera Publishing, 2026)
This study aims to analyze the influence of leadership style, organizational culture, and motivation on the job satisfaction of assistant expenditure treasurers at PTNBH University. The research method used is quantitative with a survey approach. The research sample consisted of 120 respondents selected using a purposive sampling technique. The research instrument was a questionnaire with a five-point Likert scale, which was tested for validity and reliability before use. Data were analyzed using multiple linear regression methods. The results of the study indicate that (1) leadership style has a positive and significant effect on job satisfaction; (2) organizational culture has a positive effect on job satisfaction; and (3) motivation has a significant effect on job satisfaction. Simultaneously, these three independent variables contribute significantly to the job satisfaction of assistant expenditure treasurers. These findings emphasize the importance of participatory leadership practices, strengthening organizational culture, and motivation-enhancing strategies in creating job satisfaction for administrative employees in the PTNBH environment.